A novel application perspective of the clinical-used drug verapamil on osteoporosis via targeting Txnip - Xiankun Cao; Kewei Rong; Yinghua Li; Pu Zhang; Kexin Liu; Lei Cui; Shaotian Fu; Qi Hua; Xiao Yang; Hang Zhang; Xiaofei Cheng; Peixiang Ma; et al. (Journal of Orthopaedic Translation, 2025)
Background: RANKL and SCLEROSTIN antibodies have provided a strong effective choice for treating osteoporosis in the past years, which suggested novel molecular target identification and therapeutic strategies development are important for the treatment of osteoporosis. The therapeutic effect of verapamil, a drug previously used for cardiovascular diseases, on diabetes was due to the inhibition of TXNIP expression, which has also been reported as a target in mice osteoporosis. Whether verapamil-inhibited TXNIP expression is related to osteoporosis and how it works on the molecular level is worthy to be explored. Methods: The polymorphism genotyping analysis was performed on patients with different degrees of osteoporosis. The responsiveness of bone marrow-derived macrophage cells (bone marrow-derived mesenchymal stem cells) to verapamil was evaluated by CCK-8, TRAP staining assay (ALP and AR staining assay), Bone Resorption Assay, and RNA-Sequencing. The expression and cytoplasmic efflux of ChREBP were determined by western blotting and immunofluorescence. Bilateral ovariectomy models were created, rescued by verapamil injection and the effectiveness was evaluated by Micro-CT and Histological analysis. Results: Here we discovered that rs7211 single nucleotide polymorphism (SNP) of TXNIP is closely associated with increased femur neck bone mineral density (BMD) and decreased osteoporosis rate, suggesting the importance of TXNIP in the development of osteoporosis. Verapamil suppresses Txnip expression, reduces bone turnover rate and thus rescues ovariectomy-induced mice bone loss. Mechanistically, verapamil promoted ChREBP cytoplasmic efflux, regulated Pparγ expression both mediating Txnip-MAPK, NF-κ B axis in osteoclasts, and suppressed the ChREBP-Txnip-Bmp2 axis in osteoblasts. Conclusions: The results of our study show the correlation of rs7211 TXNIP-T allele with Chinese increased femur neck BMD and decreased osteoporosis rate. In addition, verapamil can rescue mice from osteoporosis by regulateing ChREBP, Pparγ-Txnip-MAPK, NF-κ B axis in osteoclasts and ChREBP-Txnip-Bmp2 axis in osteoblasts. The translational potential of this article: The inhibition of Txnip by verapamil in osteoclasts and osteoblasts leads to low bone turnover and reduced bilateral ovariectomy-induced mice bone loss, which points out its great clinical translation potential on postmenopausal osteoporosis treatment.